Longitudinal associations between paternal mental health and child behavior and cognition in middle childhood - Jones, Sherri Lee; Caccese, Christina; Davis, Kelsey P.; Lew, Jimin; Elgbeili, Guillaume; Herba, Catherine M.; Barnwell, Julia; Robert, Cindy Hénault; Gavanski, Isabella; Horsley, Kristin; Fraser, William D.; Da Costa, Deborah; et al. (Frontiers in Psychology, 2023)
Paternal mental health has been associated with adverse consequences on offspring psychosocial development, and family environmental factors may partly explain those associations. To clarify this, we need comprehensive prospective studies, particularly in middle-childhood when the child enters school and is expected to make use of behavioral and cognitive skills as part of their interactions and learning. Using data from a sub-sample of the prospective 3D birth cohort study comprised of mother-father-child triads, and a follow-up of the parents and the children at 6-8 years of age (n=61; 36 boys, 25 girls), we examined whether paternal anxious and depressive symptoms measured during the pregnancy period (i.e., prenatally) or concurrently when the child was assessed at 6-8 years old were associated with children's cognition/behavior. In contrast to our hypotheses, we found that greater prenatal paternal depressive symptoms predicted fewer child behavioral difficulties; and that greater concurrent childhood paternal depression or anxiety symptoms were associated with higher child full-scale IQ, controlling for the equivalent maternal mental health assessment and parental education. Father parenting perception did not mediate these associations, nor were they moderated by maternal mental health at the concurrent assessment, or paternal ratings of marital relationship quality. These findings suggest that higher symptoms of paternal mental health symptoms are associated with fewer child behavioral difficulties and higher cognitive performance in middle childhood. Potential clinical implications and future research directions are discussed.